المونولوج الدرامي عند كونستانس نادين: صوت اللامنتمي - العربي, نور (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تناقش هذه الدراسة الطرق التي استخدمت بها الشاعرة الفيكتورية كونستانس نادين اسلوب المونولوج الدرامي كوسيلة لتقوية الهوية الانثوية واكتساب الصوت النسوي. يستكشف هذا البحث على الجوانب والوظائف الرئيسة للمونولوج الدرامي التقليدي وفحص الطرق التي ابتعدت بها نادين عن هذه التقاليد: اولاً عن طريق إعادة تعريف مفهوم اللامنتمي، و ثانياً عن طريق اعطاء المرأة دور المتكلم الفاعل في القصيدة و ترك دور المستمع الصامت للرجل. يقوم البحث بدراسة هذه الأفكار من خلال أربع من أهم قصائد المونولوج الدرامي لنادين و هي: "عالم الفضاء،" "الراهبة الكرملية،" "الاعتراف،" و "ملاك الرحمة." This paper discusses the ways in which Constance Naden, a major female Victorian poet, used the dramatic monologue genre as a tool for female empowerment and for the acquisition a female voice. It explores the major aspects and functions of traditional dramatic monologues and examines the ways in which Naden departed from these traditions: Firstly by redefining the character of the misfit, and secondly by giving the female the role of the active speaker, rendering the male a mere passive silent listener. These aspects are mainly studied in the light of four of Naden's major monologues: "The Astronomer," "The Carmelite Nun,""The Confession," and "The Sister of Mercy."